A microbolometer fabrication process using polymorphous silicon–germanium films (pm‐SixGey:H) as thermosensing material. Issue 7 (23rd April 2016) - Calleja, Cesar; Torres, Alfonso; Moreno, Mario; Rosales, Pedro; Sanz‐Pascual, María Teresa; Velázquez, Miguel
Abstract : For uncooled resistive microbolometers, the properties that are necessary in the thermosensing materials in order to obtain high responsivity and detectivity are a high temperature coefficient of resistivity (TCR), low resistivity, and low noise. The most used materials for these applications are boron‐doped amorphous silicon (a‐Si:H, B) and amorphous silicon–germanium (a‐Si x Ge y :H), however, those materials present some drawbacks such as relatively low TCR values and poor stability. In this work, we performed the deposition and electrical characterization of hydrogenated polymorphous silicon–germanium films (pm‐Si x Ge y :H) deposited by plasma‐enhanced chemical vapor deposition (PECVD), using a standard frequency of 13.56 MHz. We found that these films have high values of activation energy ( E a  = 6.2 eV), a thermal coefficient of resistance (TCR = 8% K −1 ), and room temperature conductivity ( σ RT  = 2.38 × 10 −8  Ω −1  cm −1 ), which are superior characteristics to those of microbolometers based on a‐Si:H and a‐Si x Ge y :H films, contained in very large commercial infrared focal plane arrays (IRFPAs).